Comparison of anterior chamber depth measurements using the IOLMaster, scanning peripheral anterior chamber depth analyser, and anterior segment optical coherence tomography. Issue 8 (27th February 2007) - Lavanya, Raghavan; Teo, Livia; Friedman, David S; Aung, Han T; Baskaran, Mani; Gao, Hong; Alfred, Tamuno; Seah, Steve K; Kashiwagi, Kenji; Foster, Paul J; Aung, Tin
Abstract : Aim: To compare anterior chamber depth measurements by three non-contact devices—the IOLMaster, scanning peripheral anterior chamber depth analyser (SPAC), and Visante anterior segment optical coherence tomography (AS-OCT) Methods: Prospective, cross sectional study of 497 phakic subjects over 50 years of age attending a community clinic in Singapore. Anterior chamber depth of the right eye was measured using all three techniques by the same investigator. Depth measurements were made from the corneal epithelium to the anterior lens surface. The values obtained were compared using Bland–Altman analysis. Results: 232 men and 265 women were examined (mean (SD) age, 63.4 (7.9) years). Mean anterior chamber depth was 3.08 (0.36) mm with IOLMaster, 3.10 (0.44) mm with SPAC, and 3.14 (0.34) mm with AS-OCT. A significant difference was present between the anterior chamber depth measurements recorded by the three devices (p<0.0001). Mean differences between the measurements were: AS-OCT v IOLMaster, 0.062 (0.007) mm (95% limits of agreement, −0.37 to 0.25 mm) (p<0.0001); AS-OCT v SPAC, 0.035 (0.011) mm (−0.44 to 0.51 mm) (p = 0.0001); SPAC v IOLMaster, 0.027 (0.012) mm (−0.57 to 0.50 mm) (p = 0.027). Conclusions: AS-OCT gave systematically deeper anterior chamber measurements than SPAC and IOL-Master. However, as the differences found were small they are unlikely to be clinically important.